2010
DOI: 10.3905/jai.2011.13.3.067
|View full text |Cite
|
Sign up to set email alerts
|

The Iconic Boom in Modern Russian Art

Abstract: Abstract:This paper investigates the prices and the returns in the market for modern Russian art, a prime example of an 'emerging art market', over the last four decades. After applying a hedonic regression model on an extensive dataset containing 52,154 sales by 410 Russian artists, we show that the reputation of the artist, the strength of the attribution, and the topic of the work play important roles in the price formation of Russian art, in addition to characteristics such as size, medium and the identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Most importantly, for many artists' output, the demand will be the highest in their home country, as collectors generally seem to prefer art from compatriots. In recent years, this has been particularly obvious in emerging markets such as China, India, and Russia, where the new rich are buying back their heritage (e.g., Renneboog and Spaenjers 2011). However, survey evidence indicates that a home bias in taste is also relevant in developed economies.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, for many artists' output, the demand will be the highest in their home country, as collectors generally seem to prefer art from compatriots. In recent years, this has been particularly obvious in emerging markets such as China, India, and Russia, where the new rich are buying back their heritage (e.g., Renneboog and Spaenjers 2011). However, survey evidence indicates that a home bias in taste is also relevant in developed economies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that the return on stocks, people's real income, and consumer demand for luxurious artworks are the key factors determining the value of art [6]. The return on art is extraordinarily high in fast-growing regions like China, Russia, and the Middle East, attributed to the enormous income inequality and the significant increase in personal wealth of few persons in these regions [4].…”
Section: Similar Art Collection Investment Analysismentioning
confidence: 99%